2020
DOI: 10.3389/fmars.2020.541853
|View full text |Cite
|
Sign up to set email alerts
|

Skin Mucus of Marine Fish as a Source for the Development of Antimicrobial Agents

Abstract: Fish skin mucus is an important component of the innate immune mechanism and provides a first barrier against pathogens. Although several studies investigated and demonstrated the antimicrobial properties of skin mucus of fishes, most of them tested antimicrobial properties against marine microbial strains as potential use in aquaculture. Furthermore, most of these studies concerned freshwater species, and far less attention was given to skin mucus of marine fishes for potential application in human health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 36 publications
0
22
1
Order By: Relevance
“…Exposed to an aquatic environment full of microbiota, fish usually develop their own immunity to safeguard against pathogens [81][82][83]. As a front-liner and paramount component of the innate immune system, fish mucus possesses a broad array of proteins and enzymes such as lysozyme, immunoglobulin, complement proteins, lectins and proteolytic enzymes that can phagocytose and digest microorganisms [84][85][86][87][88][89][90]. Furthermore, it constantly secretes and sloughs off the skin to avoid adherence and prolonged colonisation by parasites [84][85][86][87][88][89].…”
Section: Antimicrobial Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposed to an aquatic environment full of microbiota, fish usually develop their own immunity to safeguard against pathogens [81][82][83]. As a front-liner and paramount component of the innate immune system, fish mucus possesses a broad array of proteins and enzymes such as lysozyme, immunoglobulin, complement proteins, lectins and proteolytic enzymes that can phagocytose and digest microorganisms [84][85][86][87][88][89][90]. Furthermore, it constantly secretes and sloughs off the skin to avoid adherence and prolonged colonisation by parasites [84][85][86][87][88][89].…”
Section: Antimicrobial Effectsmentioning
confidence: 99%
“…As a front-liner and paramount component of the innate immune system, fish mucus possesses a broad array of proteins and enzymes such as lysozyme, immunoglobulin, complement proteins, lectins and proteolytic enzymes that can phagocytose and digest microorganisms [84][85][86][87][88][89][90]. Furthermore, it constantly secretes and sloughs off the skin to avoid adherence and prolonged colonisation by parasites [84][85][86][87][88][89]. Hence, fish skin mucus is regarded as a potential antibacterial therapeutic agent [91,92].…”
Section: Antimicrobial Effectsmentioning
confidence: 99%
“…While mucus can facilitate microbial adhesion and provide a protective matrix and nutrients for microbial growth [99], it can also be antagonistic to microbes. Fish mucus chemistry, although focused primarily on teleosts, reveal diverse antimicrobial molecules, including lysozyme and proteases [100,101]. While the chemistry of elasmobranch mucus is more sparsely characterized, studies of skin mucus from two species have also identified antimicrobial compounds, including a C-type lectin in mucus of the Japanese bullhead shark (Heterodontus japonicas) and pentraxin, an antimicrobial pectin from mucus of the common skate (Raja kenojei) [102,103].…”
Section: Skin/mucus-associated Microbesmentioning
confidence: 99%
“…Today, because of the outbreak of new infectious diseases and antibiotic-resistant bacteria, it is necessary to use novel antimicrobial compounds with various chemical formations which have new action mechanisms. These reasons have forced researchers to look for new antibiotics from various renewable natural sources such as marine origin materials (4,5), citrus extract (6), natural oils (7), medicinal herbs like ginger (8), garlic (9), etc.…”
Section: Introductionmentioning
confidence: 99%